EFL Learners’ Views on the Use of Code-Switching in Reducing Speaking Anxiety - Sholikhah, Mar'atus; Isnaini, Moh Hasbullah (VELES Voices of English Language Education Society, 2024)
Anxiety is a common obstacle for students in English speaking classes. Many EFL (English as a Foreign Language) students struggle with speaking anxiety which makes them have to switch languages from their L1 and known as code-switching (CS). While previous studies have highlighted the benefits of CS in English language learning, particularly in speaking, little attention has been given to specifically investigating its use by senior high school students to lower their speaking anxiety. Therefore, this study aims at investigating the types of CS employed by students in the classroom and to understand the student’s opinions about their experience on the influence of CS used by them to reduce their speaking anxiety. This exploratory study employed observation and interviews for data collections. This study found that students use three types of CS during speaking in English language classes, namely tag-switching, intra-sentential switching, and inter-sentential switching. Additionally, it is found that CS plays an important role in reducing students' speaking apprehension, fear of negative evaluation, and test anxiety. This research highlights the importance of CS in addressing speaking anxiety among EFL learners. Educators can use this understanding to tailor instructional approaches and provide better support for students in their language acquisition journey.